A measurement of the K + → π + μ + μ − decay - The NA62 collaboration; E. Cortina Gil; A. Kleimenova; E. Minucci; S. Padolski; P. Petrov; A. Shaikhiev; R. Volpe; T. Numao; Y. Petrov; B. Velghe; V. W. S. Wong; et al. (Journal of High Energy Physics, 2022)
Abstract A sample of 2.8 × 104 K + → π + μ + μ − candidates with negligible background was collected by the NA62 experiment at the CERN SPS in 2017–2018. The model-independent branching fraction is measured to be (9.15 ± 0.08) × 10 −8, a factor three more precise than previous measurements. The decay form factor is presented as a function of the squared dimuon mass. A measurement of the form factor parameters and their uncertainties is performed using a description based on Chiral Perturbation Theory at O $$ \mathcal{O} $$ (p 6).